ANALISIS PERSPEKTIF PEMBELAJARAN DAN PERTUMBUHAN DALAM MENGUKUR KINERJA INSTALASI FARMASI RSUD A.M. PARIKESIT TENGGARONG KUTAI KARTANEGARA KALIMANTAN TIMUR DENGAN PENDEKATAN Balanced Scorecard: Analisis Perspektif Pembelajaran Dan Pertumbuhan Dalam Mengukur Kinerja Instalasi Farmasi RSUD A.M. Parikesit Tenggarong Kutai Kartanegara Kalimantan Timur Dengan Pendekatan Balanced Scorecard - Tria Saputra Saharuddin; Satibi Satibi; Tri Murti Andayani (Jurnal Ilmiah Manuntung, 2019)
Pharmacy Department A.M. Parikesit Regional General Hospital always working to improve the quality of service, analyses is need to find the performance in Pharmacy Department A.M. Parikesit Regional Public Hospital. The concept of the balanced scorecard is a performance evaluation tool that is comprehensive, coherent and relevant to be applied in hospitals for improving the performance of every aspect of total. The study to evaluate the performance Pharmacy Department A.M. Parikesit Regional General Hospital through learning and growth perspective. This research used non experimental case study arrangement research the explorative descriptive approach. Data collection was retrospective and prospectively in the form of quantitive data. Qualitative data was obtained by questionnaires, depth interview with the head of Pharmacy Departmen A.M. Parikesit. The quantitative data obtained through direct observation and personnel file. The results of research with the used balanced scorecard at a performance perspective learning and growth shown that: a. human capital: Good category productivity of employess, the level of employee productivity is 86.73%, the percentage of employees who received training in 2013, 2014 and from January to July 2015 is respectively for 15.38%, 32.25% and 97, 72%, the average value of the high category in morale, job satisfaction, knowledge, empskill and talent; b. information capital showed the average category of high on the aspect of information technology, a database and network, but need the information management system updates for support the management and drug reporting and need to improve communication with the customer network.; c. organization capital showed the value of the average category of high on the aspect of cultural organization ,leadership and alignment.